Sikap Toleransi Beragama pada Generasi Milenial di Desa Tlogopatut Kecamatan Kebomas Kabupaten Gresik - Hasanah, Muhimmatul; Zunaih, Ahmad Iwan; Musbikhin, Musbikhin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Tolerance in inter-religious relations, which is based on each religion, is the responsibility of the believers themselves. Worship (ritual) is a form of worship that has an accepted system and method, and everyone who adheres to it must follow it. Tlogopatut Village is located in Kebomas, Gresik. Here there are several houses of worship and six religions: Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism. This village is considered a community of religious moderation because the people get along well and have never been involved in conflict. The purpose of this study is to determine the attitude of religious tolerance shown by the millennial generation as adherents of other religions and interfaith cooperation in the millennial generation. The focus of this qualitative research is the millennial generation in Tlogopatut Village. Researchers used interview and observation instruments. The results showed that millennial teenagers show three attitudes, namely mutual acceptance, mutual respect, and mutual appreciation, in life between religious believers and also continue to treat their friends well even though they are of different religions.